Vibrational analysis of faulty deep-groove ball bearing under radial load - More, Kiran; Honawadajkar, Pranoti; Kandharkar, Sachin; Tidke, Bharat; Pawar, Rahul B.; Shende, Mangesh; Kherde, Rajesh; Kawade, Ganesh; Patil, Sachin (Frontiers in Mechanical Engineering, 2025)
IntroductionDeep-groove ball bearings are widely used in industrial applications due to their ability to support radial and axial loads simultaneously. However, prolonged operation under harsh conditions can lead to localized defects such as inner race, outer race, or rolling element faults. These defects often manifest as distinct vibration patterns, which can be detected and analyzed to diagnose bearing health. This study focuses on the vibrational analysis of faulty deep-groove ball bearings under radial load, aiming to establish a correlation between fault characteristics and vibration signatures.MethodsA specialized test rig evaluates the vibration responses of deep-groove ball bearings under controlled conditions, capturing data in both time and frequency domains for comprehensive analysis. Vibration signals from healthy and defective bearings are analyzed to ensure precision and reliability. The study identifies characteristic fault frequencies and harmonics caused by localized defects on the inner or outer race, comparing simulated and experimental data. This approach provides insights into how defect types and load conditions influence bearing vibration signatures.ResultsThe evaluation of single and multiple defects shows higher velocity amplitudes for multiple defects. Time-domain analysis reveals that a single inner race defect under a 5 kg radial load has a velocity amplitude of 2.00 mm/s, while two defects on the inner race under the same load result in a slightly lower amplitude of 1.88 mm/s.DiscussionThe experimental findings closely match the simulation results, showing a strong correlation between the two methods. Further analysis using orbit analysis is conducted to examine the behavior of deep-groove ball bearings under similar conditions.